Public Anxiety and the Implementation of the Covid 19 Vaccine - Amas, Rizky Rahayu; Wardanengsih , Ery; Barangkau (Bantayang Omni Cendekia, 2024)
Background: Anxiety is a feeling experienced by a person making him uneasy which is haunted by his own thoughts. The implementation of the COVID-19 vaccine is a way to increase immunity in the body so as to limit the spread of certain diseases in the human body. Objective: The purpose of the study was to determine the relationship between public anxiety and the implementation of the covid 19 vaccine. Methods: This study was quantitative research with an accidental sampling approach. The sampling technique in this study was the elderly who have never received Covid-19 vaccine and were willing to as many as 35 samples, using the Chi-Square Test. Results: Majority of respondents experienced moderate anxiety, totaling 21 (60%) respondents and most of them were disagree receiving the Covid-19 vaccine, accounting for 21 (60%) respondents. According to the Chi-square test, the p-value was 0.000 (<0.05). This indicated that there was a correlation between public anxiety and the implementation of the Covid-19 vaccine. Conclusion: There is a relationship between public anxiety and the implementation of the Covid-19 vaccine in one of public health centers in Wajo Regency.